Can conservation‐oriented, captive breeding limit behavioural and growth divergence between offspring of wild and captive origin Atlantic salmon (Salmo salar)?. Issue 2 (10th May 2014) - Wilke, Nathan F.; O'Reilly, Patrick T.; MacDonald, Danielle; Fleming, Ian A.
Abstract: Captive rearing is being used increasingly to maintain demographics and genetic diversity of threatened fish populations and species, but its effectiveness can be hindered by domestication, that is, inadvertent selection for performance in captivity at the cost of that in the wild. Some captive rearing programmes have begun to take steps to limit such domestication, but the results are ambiguous, as the degree of generational exposure to captivity is often difficult to control. Using an endangered population of Atlantic salmon ( Salmo salar ) currently undergoing conservation‐oriented captive rearing, we tested for domestication effects on dominance (dyadic trials) and growth (seminatural stream channels with differing densities and group proportions) of juvenile offspring of wild and captive origin parents. Pedigree data afforded the ability to compare these effects among three specific study groups: wild, single‐generation captives and two to three generation captives. Our results indicate that, despite conservation breeding practices, a divergence in growth can occur in as little as one generation without divergence in dominance behaviour. Further, evidence suggests that trait divergence did not increase with generations in captivity. Given the experimental design, results and supporting literature, we conclude that this contemporary divergence is likely genetic and driven by a combination of factors, including variation in selective histories influencing behaviour.